Analysis Of Swiftlet Farming Income In Improving The Community’s Economy Of Parisan Agung Village Dampelas, Donggala Regency - Wahyuni; Rahma Masdar; Abdul Kahar; Mustamin (CV. Doki Course and Training, 2025)
Indonesia is a country with abundant biological resources. If managed appropriately. One of the potential biological natural resources is the swallow, which can provide great benefits, both ecologically and economically. In Parisan Agung Village, Dampelas District, Donggala Regency is one of the places that produce swallow nests which are quite numerous. There are approximately 40 houses that have swallow buildings. The purpose of this study is to understand how the swallow's nest business can contribute to increasing the income of the people of Parisan Agung Village, Dampelas District, Donggala Regency. The method used is a descriptive modus operative of qualitative data presented in the form of revenue data obtained from companies engaged in the swallow's nest business. Revenue in the swallow's nest business amounted to IDR 6,032,500,000 and total expenses incurred were IDR 5,531,300,000 and business results received amounted to IDR 501,200,000. The swallow business in Parisan Agung Village, Dampelas District, Donggala Regency can improve the community's economy and be profitable.